KEKUATAN HUKUM PUTUSAN SECARA MEDIASI DALAM KASUS ALAT PIJAT (SLIMING DIGIT) YANG MENGALAMI KERUSAKAN DI BADAN PENYELESAIAN SENGKETA KONSUMEN KOTA DENPASAR - Dwi Pranata, Made; Sri Indrawati, A. A.; Rudy, Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014, 2014)
The title that increase in writing this Journal is the power of law in the mediasion of massage tool case (sliming digis) at BPSK (institution of law) in Denpasar city. The aim in this study is to find the power of letter of peace agreement by mediation in massage tool case (sliming digis) as BPSK Denpasar city. The method used in this study was yuridis empiris method. Accounting to the problem and the aim of this study, the conclusion found that the power of letter of peace agreement by the mediation as BPSK in Denpasar city already final and bond, remember all things that related with resolve the despute by mediation are pure declare base on the parries agreement.
Keywords: BPSK, Mediation, Agreement